Perindopril alleviates inflammation via Cyclooxygenase inhibition: a bioinformatics, in vitro and in vivo evaluation - El Sebaei, Mahmoud; Zabady, Mohamed Karam; Ghonim, Ibrahim; Hereba, Abdulrahman Taha; Abdelghany, Ahmed Meligy; El-Bahr, Sabry Mohamed; Gaballa, Mohamed Mahmoud Salem Ahmed; Kandeel, Mahmoud (International journal of pharmacology, 2023)
Background and Objective: Perindopril (PER), an angiotensin-converting enzyme (ACE) inhibitor with anti-apoptotic, antioxidant and anti-inflammatory characteristics, has long been used to treat cardiovascular illnesses. In this study, the enzyme inhibitory activity of PER against Cyclooxygenase-1 (COX-1) and Cyclooxygenase-2 (COX-2) was determined. Materials and Methods: The PERʼs anti-inflammatory actions were estimated by in vitro COX-1 and COX-2 inhibition assays, the in vivo rat model of carrageenan-induced paw edema, histopathological examination, molecular modeling, docking and molecular dynamics studies. The data were analyzed using the Analysis of Variance (ANOVA) Test. Results: The PER IC50 values for COX-1 and COX-2 were calculated to be 8.3 and 0.1 µM, respectively, showing that PER has an 85.5-fold higher affinity for COX-2 than for COX-1. The PER was found to be a moderate inflammation suppressor in rat paw assay, comparable to celecoxib and indomethacin. Docking and molecular dynamics (MD) simulation supported the stable binding of PER with COX-2. Conclusion: Current findings revealed that PER can be used for local acute inflammation and utilized as a substitute for other topical anti-inflammatory medicines, particularly those containing steroids.
Gesehen am 09.09.2024